Abrasion-resistant universal joint and preparation method of surface coating of abrasion-resistant universal joint
By designing the flange and oblique groove structure on the universal joint and coating with high-entropy alloy and amorphous alloy composite coating, the problems of wear, erosion and corrosion of the universal joint during drilling are solved, and the transmission efficiency and service life are improved.
Patent Information
- Application Number
- CN202411780217.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-18
AI Technical Summary
Universal joints are susceptible to wear, erosion and corrosion during drilling, resulting in reduced transmission efficiency and shortened service life.
By designing the flap and oblique groove structure on the universal joint and applying a composite coating composed of high-entropy alloy and amorphous alloy on its surface, the corrosion resistance, corrosion resistance and wear resistance of the universal joint are improved.
It significantly improves the transmission efficiency and service life of the universal joint, reduces the friction coefficient of the surface, and makes it more suitable for complex and variable drilling environments.
Smart Images

Figure CN119640192A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of geological drilling and drilling tools, and relates to a method for preparing a wear-resistant universal joint and a surface coating thereof. Background Art
[0002] With the continuous development of drilling technology, deep drilling technology is also making new breakthroughs. The number of wells with a depth of 10,000 meters or even more than 10,000 meters is gradually increasing. As a commonly used drilling tool in the drilling process, screw drilling tools have become an important part of oil and gas development. Screw drilling tools are mainly composed of bypass valves, motors, universal joints and drive shafts. Among them, the universal joint is a key component of screw drilling tools. It connects the motor rotor that performs planetary motion in the motor assembly and the drive shaft that performs fixed-axis motion, converts the output torque of the motor rotor into the fixed-axis rotation of the drive shaft, and then transmits it to the drill bit to perform drilling operations.
[0003] When the universal joint is working, not only will rotational wear occur between the universal joint teeth, but it will also be eroded and corroded by the immersion and flow of drilling fluid, and the cuttings carried by the drilling fluid will also abrade the universal joint, which will lead to increased abrasion of the universal joint, reduced transmission efficiency, and in severe cases, jamming and failure, affecting the safe operation of the screw drill. Due to the complex and changeable service environment and harsh working conditions of the universal joint, there are higher requirements for its working efficiency and service life, so the surface of the universal joint needs to be strengthened. Common surface strengthening measures include forming an alloy coating on the surface of the universal joint to improve its structural strength and wear resistance.
[0004] CN 202946039U discloses a universal shaft housing, which consists of a front housing, a rear housing, a pipe sleeve and a wear-resistant layer. The front housing and the rear housing are connected at an obtuse angle, and the radial dimensions of the front and rear housings are the same. The pipe sleeve is fixed on the outer layer of the front housing and the rear housing, and the wear-resistant layer is evenly coated on the outer surface of the pipe sleeve. The wear-resistant layer is coated with an Armacor amorphous alloy layer on the outer layer. The patent only discloses that the outer side of the universal shaft is provided with an amorphous alloy layer, and does not improve the structure of the universal shaft, and does not explain the specific composition of the coating.
[0005] CN 114990465A discloses a wear-resistant blade and its preparation method and application, wherein the blade comprises a blade substrate, an Al2O3 layer having a multi-layer structure located on the surface of the substrate, and a xCoCrFeNi high entropy alloy coating and an adjustment layer arranged between any two adjacent layers of high entropy alloy coating; the atomic percentage of Al in each layer of the high entropy alloy coating increases successively from the blade substrate to the blade surface, wherein the range of x is 0 to 2. The surface of the blade substrate is provided with multiple layers of high entropy alloy coatings separated by adjustment layers. The coating structure is relatively complex and requires multiple thermal spraying treatments and vacuum heat treatments. The large number of layers increases the instability of the coating. The blade is used for a turbine drill, and unlike the universal joint structure, it does not involve improvements to the structure of the turbine blade itself.
[0006] CN 115141998A discloses an amorphous alloy coating and a preparation method thereof, the method comprising: providing a substrate; preparing an amorphous alloy powder; and spraying the amorphous alloy powder onto the surface of the substrate by a thermal spraying method to form an amorphous alloy coating. Although the method also involves the use of a thermal spraying method to prepare an amorphous alloy coating, the application field is different. When it is used in non-stick cookware, the requirements for abrasion resistance are significantly lower than those when it is used in drilling tools, so the composition selection of the coating will also be different. It does not involve the common use of high entropy alloys and amorphous alloys, and the process of using alloy coatings of different compositions at different positions of the substrate.
[0007] In summary, for the structure of components such as universal joints in drilling tools, it is necessary to optimize the structure of universal joints according to application requirements and prepare wear-resistant composite coatings to improve erosion resistance, corrosion resistance and abrasion resistance and increase service life. Summary of the invention
[0008] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing a wear-resistant universal joint and its surface coating. Through the petal tooth design on the universal joint and the structural design of the oblique groove on the petal tooth, the erosion resistance, corrosion resistance and wear resistance of the universal joint can be effectively improved, the transmission efficiency and service life can be improved, and through the design of composite coatings with different compositions on the petal teeth and the inner wall of the oblique groove, the coating has excellent mechanical properties and wear resistance, reduces the surface friction coefficient, and improves the comprehensive performance of the universal joint.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] On the one hand, the present invention provides a wear-resistant universal joint, characterized in that the universal joint comprises a universal joint base and universal joint petals, the universal joint petals are located above the universal joint base, at least three universal joint petals are provided, such as three, four, five or six, etc., which are evenly distributed along the circumference, and the universal joint petals are inclined compared to the universal joint base; the surface of each universal joint petal is provided with a plurality of parallel oblique grooves, and the surface of the universal joint petal and the inner wall of the oblique groove are coated with a composite coating, and the composite coating is composed of a high entropy alloy and an amorphous alloy.
[0011] In the present invention, according to the application of the universal joint, in order to overcome the problems of large wear of the petal teeth of the traditional universal joint and poor surface erosion and corrosion resistance, the structure of the universal joint is optimized and designed, and the petal teeth on the universal joint and the oblique grooves on the petal teeth are designed to increase the contact area between the petal teeth of the universal joint and between the drilling fluid and the universal joint while ensuring the overall structural strength and rigidity of the universal joint, thereby reducing the erosion and corrosion effects of the drilling fluid on the surface of the universal joint; by re-coating a composite coating on the surface of the universal joint and selecting a high entropy alloy and an amorphous alloy, the wear resistance of the universal joint is further improved, the friction coefficient of the surface is effectively reduced, the transmission efficiency between the motor rotor and the transmission shaft is improved, and the service life of the universal joint is improved, so that it can better adapt to complex and changeable service environments; the universal joint structure is reasonably designed, the improvement method is simple, the improvement effect is significant, and the scope of application is wide.
[0012] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0013] As a preferred technical solution of the present invention, the universal joint petal teeth are in a convex shape and connected to the universal joint base with rounded corners. The width of the convexity first decreases, then increases, and finally decreases from bottom to top.
[0014] Preferably, the changes in the width of the universal joint petal teeth are all achieved by arc-shaped connection.
[0015] Preferably, the inclination angle of the universal joint petal teeth relative to the universal joint base is 5 to 10°, for example 5°, 6°, 7°, 8°, 9° or 10°, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. The inclination direction of the universal joint petal teeth is consistent with the rotation direction of the motor rotor in the screw drill.
[0016] In the present invention, the universal joint petal teeth have a certain inclination angle, which can not only increase the contact area between the petal teeth and improve the transmission efficiency, but also reduce the erosion and corrosion of the drilling fluid and the mutual wear between the petal teeth; and the design of the inclination angle and inclination direction can ensure that the petal teeth will not affect the strength and stiffness parameters of the universal joint due to excessive inclination. On the basis of ensuring that the strength and stiffness meet the requirements and thus ensure the stability of the overall structure, it can withstand greater torque, reduce the stress on the root of the petal teeth caused by the transmitted torque, and improve the torque transmission efficiency.
[0017] In the present invention, when processing the universal joint petal teeth, a CNC machine tool is used to perform cutting processing according to a written program. After the overall shape processing is completed, a milling machine is used to perform polishing and grinding to maintain the smoothness of the universal joint surface, which is beneficial to the subsequent deposition of a high-entropy amorphous alloy composite coating.
[0018] As a preferred technical solution of the present invention, the number of the oblique grooves on each of the universal joint petal teeth is at least two, which are evenly distributed on the surface of the universal joint petal teeth, and the width between two adjacent oblique grooves is not less than 3 cm, for example, 3 cm, 3.2 cm, 3.5 cm, 3.8 cm, 4 cm, 4.2 cm, 4.5 cm, 4.8 cm or 5 cm, etc., but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, the distance between the oblique groove and the edge of the universal joint petal tooth is not less than 5 cm, for example 5 cm, 5.2 cm, 5.5 cm, 5.8 cm, 6 cm, 6.3 cm, 6.5 cm, 6.8 cm or 7 cm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] Preferably, the oblique groove is opened along the running direction of the motor rotor in the screw drill, and its inclination angle compared to the cross-section of the universal joint base is 20 to 45°, for example, 20°, 25°, 30°, 35°, 40° or 45°, etc., but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0021] In the present invention, the mutually parallel oblique grooves are arranged on the universal joint teeth, which can also increase the contact area between the universal joint teeth and the drilling fluid, reduce the erosion effect of the drilling fluid on the surface, accelerate the flow of the drilling fluid, and increase the life of the universal joint.
[0022] As a preferred technical solution of the present invention, the oblique groove is in the shape of an elongated strip as a whole, and the width of the oblique groove is 2 to 4 cm, for example, 2 cm, 2.5 cm, 2.7 cm, 3 cm, 3.2 cm, 3.5 cm or 4 cm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] Preferably, the oblique groove has no right-angle area at the groove mouth, and the long side and short side of the oblique groove are connected by a rounded corner, and the arc length of the rounded corner is not greater than 3mm, for example, 3mm, 2.7mm, 2.5mm, 2.2mm, 2mm, 1.8mm or 1.5mm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] Preferably, at least two grooves are provided on the two long sides of the oblique groove, for example, two, three or four, and the width between adjacent grooves is not greater than 2 mm, for example, 2 mm, 1.8 mm, 1.6 mm, 1.5 mm, 1.2 mm or 1 mm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Preferably, the grooves on the two long sides of the oblique groove are parallel to each other and symmetrically arranged.
[0026] In the present invention, the oblique groove is composed of mutually parallel grooves, wherein the inclination direction of the groove is consistent with the flow direction of the drilling fluid. In addition, the design of the groove without a right-angle area can further reduce the erosion effect of the drilling fluid on the groove.
[0027] In the present invention, a CNC machine tool is used to mill an oblique groove on the surface area of the universal joint petal tooth, and the oblique groove is opened along the running direction of the screw drill motor rotor. The oblique grooves are evenly distributed on the surface of the petal tooth, and then sandpaper, polishing cloth, etc. are used to grind and polish the notch of the oblique groove; a milling machine is used to process the non-right-angle area of the notch of the oblique groove, and a groove is processed on the inner wall of the notch to ensure that the direction of the groove is consistent with the direction of the oblique groove, and the grooves are evenly distributed on the inner wall of the oblique groove, and then the groove is rounded.
[0028] As a preferred technical solution of the present invention, the thickness of the composite coating is 150 to 300 μm, for example, 150 μm, 160 μm, 180 μm, 200 μm, 220 μm, 250 μm, 270 μm or 300 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the content of high entropy alloy in the composite coating is 20 to 80wt%, for example 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt% or 80wt%, etc., but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0030] In the present invention, the high entropy alloy component contained in the composite coating can ensure the high entropy effect of the composite coating, so that it has good corrosion resistance and wear resistance, and effectively reduces the friction coefficient of the surface. At the same time, the amorphous alloy component can ensure the appearance of the amorphous state in the composite coating, and the amorphous alloy itself has good erosion resistance.
[0031] Preferably, the composite coating on the surface of the universal joint tooth is a first composite coating, and the content of high entropy alloy in the first composite coating is 20 to 40wt%, for example, 20wt%, 22wt%, 25wt%, 27wt%, 30wt%, 32wt%, 35wt%, 38wt% or 40wt%, etc., but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0032] Preferably, the surface of the universal joint base is also coated with a first composite coating.
[0033] Preferably, the composite coating on the inner wall of the oblique groove is a second composite coating, and the content of high entropy alloy in the second composite coating is 60 to 80wt%, for example, 60wt%, 62wt%, 65wt%, 68wt%, 70wt%, 72wt%, 75wt%, 78wt% or 80wt%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In the present invention, the composite coating has both high entropy alloy properties and amorphous alloy properties, wherein the high entropy alloy mainly plays a role in corrosion resistance, and the amorphous alloy mainly plays a role in wear resistance, while the surface of the universal joint tooth is mainly affected by wear and corrosion, and the notch of the oblique groove is mainly affected by corrosion and erosion. High entropy amorphous alloy composite coatings of different components are arranged on the surface of the universal joint tooth and the notch of the oblique groove, the former is mainly composed of amorphous alloy, and the latter is mainly composed of high entropy alloy, so as to ensure that the performance of each area of the universal joint meets the application requirements.
[0035] Preferably, the high entropy alloy in the composite coating includes a FeCoNiCr alloy or a WMoTaNb alloy.
[0036] Preferably, the amorphous alloy in the composite coating comprises any one of Fe-based alloy, Ni-based alloy or Zr-based alloy, or a combination of at least two of them. Typical but non-limiting examples of the combination include: a combination of Fe-based alloy and Ni-based alloy, a combination of Ni-based alloy and Zr-based alloy, a combination of Fe-based alloy, Ni-based alloy and Zr-based alloy, etc.
[0037] In the present invention, the types of high entropy alloys can be selected from AlCoCrFeNi alloy, FeCoNiCrMn alloy, VWMoTaNb, etc. Among the types of amorphous alloys, the elements of Fe-based amorphous alloys mainly include iron, silicon, boron, carbon, phosphorus, etc., the elements of Ni-based amorphous alloys mainly include nickel and phosphorus, and may also include copper, chromium or manganese, and the elements of Zr-based amorphous alloys mainly include zirconium, copper, iron, aluminum, etc.
[0038] Preferably, the composite coating is made of high entropy amorphous alloy composite powder obtained by uniformly mixing high entropy alloy powder and amorphous alloy powder.
[0039] On the other hand, the present invention provides a method for preparing the surface coating of the universal joint, the preparation method comprising the following steps:
[0040] (1) After the universal joint is fixed, a sandblasting roughening treatment is performed, and high entropy alloy powder and amorphous alloy powder are mixed in different proportions to prepare two high entropy amorphous alloy composite powders;
[0041] (2) thermally spraying one of the high entropy amorphous alloy composite powders onto the surface of the universal joint tooth to prepare a first composite coating;
[0042] (3) Another high entropy amorphous alloy composite powder is thermally sprayed onto the inner wall of the oblique groove of the universal joint to prepare a second composite coating.
[0043] As a preferred technical solution of the present invention, the universal joint described in step (1) is cleaned before being fixed.
[0044] Preferably, the cleaning comprises ultrasonic cleaning using an organic solvent.
[0045] Preferably, the organic solvent comprises acetone and / or ethanol.
[0046] Preferably, the power of the ultrasound is 100-150 W, for example, 100 W, 110 W, 120 W, 130 W, 140 W or 150 W, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable; the frequency of the ultrasound is 30-50 kHz, for example, 30 kHz, 32 kHz, 35 kHz, 38 kHz, 40 kHz, 42 kHz, 45 kHz, 48 kHz or 50 kHz, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0047] Preferably, the cleaning time is 10 to 20 minutes, for example 10 minutes, 12 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes or 20 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] In the present invention, the universal joint is firstly ultrasonically cleaned to remove oil stains and dirt on the surface, and then subjected to sandblasting roughening treatment to increase the roughness of the universal joint surface, thereby increasing the bonding strength between the universal joint body and the coating.
[0049] Preferably, when the universal joint is fixed in step (1), the universal joint base is fixed on a workbench.
[0050] Preferably, the sandblasting medium used in the sandblasting roughening in step (1) includes quartz sand.
[0051] Preferably, the particle size of the sandblasting medium is 1 to 2 mm, for example, 1 mm, 1.2 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.8 mm or 2 mm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Preferably, after the sandblasting roughening treatment in step (1), the surface roughness of the universal joint is 4.5 to 8.5 μm, for example, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, 6.5 μm, 7.0 μm, 7.5 μm, 8.0 μm or 8.5 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] As a preferred technical solution of the present invention, the particle sizes of the high entropy alloy powder and the amorphous alloy powder in step (1) are independently 15 to 45 μm, for example, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm or 45 μm, etc., but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] Preferably, the high entropy alloy powder includes FeCoNiCr alloy powder or WMoTaNb alloy powder.
[0055] Preferably, the amorphous alloy powder comprises any one of Fe-based alloy powder, Ni-based alloy powder or Zr-based alloy powder, or a combination of at least two of them. Typical but non-limiting examples of the combination include: a combination of Fe-based alloy and Ni-based alloy, a combination of Ni-based alloy and Zr-based alloy, a combination of Fe-based alloy, Ni-based alloy and Zr-based alloy, etc.
[0056] Preferably, in the two high entropy amorphous alloy composite powders described in step (1), the high entropy alloy powder accounts for 20 to 40 wt% in one of the composite powders, for example, 20 wt%, 22 wt%, 25 wt%, 27 wt%, 30 wt%, 32 wt%, 35 wt%, 38 wt% or 40 wt%, and the high entropy alloy powder accounts for 60 to 80 wt% in the other composite powder, for example, 60 wt%, 62 wt%, 65 wt%, 68 wt%, 70 wt%, 72 wt%, 75 wt%, 78 wt% or 80 wt%, etc.; but it is not limited to the listed values, and other unlisted values within the respective numerical ranges are equally applicable.
[0057] Preferably, the high entropy alloy powder and the amorphous alloy powder are mixed in step (1) by ball milling.
[0058] Preferably, the ball milling mixing time is 4 to 6 hours, such as 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0059] As a preferred technical solution of the present invention, the thermal spraying in step (2) is performed using a thermal spraying device, and the parameters of the thermal spraying device are debugged before the thermal spraying.
[0060] Preferably, the composite powder in step (2) is placed in a thermal spraying device, and the device parameters are adjusted until the composite powder flame flow becomes stable.
[0061] Preferably, the thermal spraying in step (2) uses a composite powder in which the high entropy alloy powder accounts for 20 to 40 wt%, such as 20 wt%, 22 wt%, 25 wt%, 27 wt%, 30 wt%, 32 wt%, 35 wt%, 38 wt% or 40 wt%, etc., and the universal joint petal teeth are placed directly above the flame flow.
[0062] Preferably, after the universal joint petal teeth are coated in step (2), the universal joint substrate is coated, and the process parameters for coating the universal joint substrate are the same as the corresponding parameters for coating the universal joint petal teeth.
[0063] Preferably, the powder feeding rate during the thermal spraying in step (2) is 50-150 g / min, for example, 50 g / min, 60 g / min, 80 g / min, 100 g / min, 120 g / min, 140 g / min or 150 g / min, the spraying distance is 180-230 mm, for example, 180 mm, 190 mm, 200 mm, 210 mm, 220 mm or 230 mm, and the moving speed of the spray gun is 300-800 mm / s, for example, 300 mm / s, 400 mm / s, 500 mm / s, 600 mm / s, 700 mm / s or 800 mm / s, etc.; however, it is not limited to the listed values, and other unlisted values within their respective numerical ranges are equally applicable.
[0064] Preferably, in step (2), fuel gas and carrier gas are used for thermal spraying, the fuel gas includes hydrogen, the carrier gas includes nitrogen and / or an inert gas, and the inert gas includes any one or at least two of helium, argon or neon.
[0065] Preferably, the flow rate of the fuel gas is 25-45 L / min, for example, 25 L / min, 27 L / min, 30 L / min, 32 L / min, 35 L / min, 38 L / min, 40 L / min, 42 L / min or 45 L / min, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable; the flow rate of the carrier gas is 20-40 L / min, for example, 20 L / min, 22 L / min, 25 L / min, 27 L / min, 30 L / min, 32 L / min, 35 L / min, 38 L / min or 40 L / min, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0066] Preferably, the temperature of the thermal spraying in step (2) is 2500-4000°C, for example, 2500°C, 2750°C, 3000°C, 3200°C, 3500°C, 3800°C or 4000°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] Preferably, the single spraying thickness during the thermal spraying in step (2) is 8 to 12 μm, for example, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm or 12 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0068] As a preferred technical solution of the present invention, the composite powder used in the thermal spraying in step (3) is a high-entropy alloy powder accounting for 60 to 80 wt%, such as 60 wt%, 62 wt%, 65 wt%, 68 wt%, 70 wt%, 72 wt%, 75 wt%, 78 wt% or 80 wt%, etc., and the direction of the flame flow in step (2) is adjusted to align with the inner wall of the oblique groove.
[0069] Preferably, the direction of the flame flow in step (3) is inclined by 40 to 50° compared to the flame flow direction in step (2), for example, 40°, 42°, 44°, 46°, 48° or 50°, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0070] Preferably, the powder feeding rate during the thermal spraying in step (3) is 50-150 g / min, for example, 50 g / min, 60 g / min, 80 g / min, 100 g / min, 120 g / min, 140 g / min or 150 g / min, the spraying distance is 180-230 mm, for example, 180 mm, 190 mm, 200 mm, 210 mm, 220 mm or 230 mm, and the moving speed of the spray gun is 300-800 mm / s, for example, 300 mm / s, 400 mm / s, 500 mm / s, 600 mm / s, 700 mm / s or 800 mm / s, but is not limited to the listed values, and other unlisted values within their respective numerical ranges are equally applicable.
[0071] Preferably, in step (3), the thermal spraying uses a fuel gas and a carrier gas, the fuel gas includes hydrogen, the carrier gas includes nitrogen and / or an inert gas, and the inert gas includes any one or at least two of helium, argon or neon.
[0072] Preferably, the flow rate of the fuel gas is 25-45 L / min, for example, 25 L / min, 27 L / min, 30 L / min, 32 L / min, 35 L / min, 38 L / min, 40 L / min, 42 L / min or 45 L / min, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable; the flow rate of the carrier gas is 20-40 L / min, for example, 20 L / min, 22 L / min, 25 L / min, 27 L / min, 30 L / min, 32 L / min, 35 L / min, 38 L / min or 40 L / min, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0073] Preferably, the temperature of the thermal spraying in step (3) is 2500-4000°C, for example, 2500°C, 2750°C, 3000°C, 3200°C, 3500°C, 3800°C or 4000°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0074] Preferably, the single spraying thickness during the thermal spraying in step (3) is 8 to 12 μm, for example, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm or 12 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0075] In the present invention, the high entropy amorphous alloy composite coating prepared by thermal spraying has small overall fluctuation and stable tribological performance in a corrosive wear environment. The deposited composite coating combines the mechanical properties, wear resistance and corrosion resistance of both the high entropy alloy and the amorphous alloy, thereby significantly improving the comprehensive performance of the universal joint.
[0076] Compared with the prior art, the present invention has the following beneficial effects:
[0077] (1) The present invention optimizes the design of the universal joint structure. By designing the petal teeth on the universal joint and setting the oblique grooves on the petal teeth, the contact area between the petal teeth of the universal joint and between the drilling fluid and the universal joint is increased while ensuring the overall structural strength and rigidity of the universal joint, thereby reducing the erosion and corrosion effects of the drilling fluid on the surface of the universal joint;
[0078] (2) The present invention further improves the wear resistance, corrosion resistance and erosion resistance of the universal joint by coating a composite coating on the surface of the universal joint and selecting different contents of high entropy alloy and amorphous alloy. The overall microhardness of the coating is above 715.0 HV, the nanohardness is above 6.9 GPa, and the elastic modulus can reach above 117.0 GPa, which effectively reduces the surface friction coefficient, improves the transmission efficiency, and increases the service life of the universal joint, so that it can better adapt to the complex and changeable service environment;
[0079] (3) The universal joint structure of the present invention is reasonably designed, the improvement method is simple, the improvement effect is significant, and the application range is wide. BRIEF DESCRIPTION OF THE DRAWINGS
[0080] Figure 1 is a schematic diagram of the overall structure of the wear-resistant universal joint provided in Example 1 of the present invention;
[0081] Figure 2 is a schematic diagram of the partial structure of the wear-resistant universal joint provided in Example 1 of the present invention;
[0082] Among them, 1 is a universal joint base, 2 is a universal joint tooth, 3 is an oblique groove, and 4 is a groove. DETAILED DESCRIPTION
[0083] In order to better illustrate the present invention and facilitate understanding of the technical solution of the present invention, the present invention is further described in detail below. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0084] The following are typical but non-limiting embodiments of the present invention:
[0085] Embodiment 1:
[0086] This embodiment provides a wear-resistant universal joint. The overall structural diagram of the universal joint is as follows: Figure 1 The local structure diagram is shown in Figure 2 As shown, it includes a universal joint base 1 and a universal joint petal tooth 2, wherein the universal joint petal tooth 2 is located above the universal joint base 1, and three universal joint petal teeth 2 are provided, which are evenly distributed along the circumference, and the angle between adjacent petal teeth is 120°, and the universal joint petal teeth 2 are inclined compared to the universal joint base 1; the surface of each universal joint petal tooth 2 is provided with a plurality of parallel oblique grooves 3, and the surface of the universal joint petal tooth 2 and the inner wall of the oblique groove 3 are coated with a composite coating, and the composite coating is composed of a high entropy alloy and an amorphous alloy.
[0087] The universal joint tooth 2 is in a convex shape and connected to the universal joint base 1 with a rounded corner. The width of the convexity first decreases, then increases, and finally decreases from bottom to top. The change in the width of the universal joint tooth 2 is achieved by an arc connection.
[0088] The inclination angle of the universal joint tooth 2 and the universal joint base 1 is 5°, and the inclination direction of the universal joint tooth 2 is consistent with the running direction of the motor rotor in the screw drilling tool.
[0089] There are three oblique grooves 3 on each universal joint tooth 2, which are evenly distributed on the surface of the universal joint tooth 2, and the width between two adjacent oblique grooves 3 is 4 cm.
[0090] The distance between the oblique groove 3 and the edge of the universal joint tooth 2 is 6 cm.
[0091] The oblique groove 3 is opened along the running direction of the motor rotor in the screw drill, and its inclination angle relative to the cross section of the universal joint base 1 is 30°.
[0092] The oblique groove 3 is in the shape of an elongated strip as a whole, and the width of the oblique groove 3 is 3 cm.
[0093] The slot opening of the oblique slot 3 has no right-angled area, and the long side and the short side of the oblique slot 3 are connected by a rounded corner, and the arc length of the rounded corner is 3 mm.
[0094] Three grooves 4 are arranged on the two long sides of the oblique groove 3, and the width between adjacent grooves 4 is 2 mm.
[0095] The grooves 4 on the two long sides of the oblique groove 3 are parallel to each other and symmetrically arranged.
[0096] The thickness of the composite coating is 240 μm.
[0097] The composite coating on the surface of the universal joint tooth 2 is a first composite coating, and the content of the high entropy alloy in the first composite coating is 20wt%.
[0098] The surface of the universal joint base 1 is also coated with a first composite coating.
[0099] The composite coating on the inner wall of the oblique groove 3 is a second composite coating, and the content of high entropy alloy in the second composite coating is 80wt%.
[0100] The high entropy alloy in the composite coating is a FeCoNiCr alloy, and specifically an AlCoCrFeNi high entropy alloy.
[0101] The amorphous alloy in the composite coating is a Fe-based alloy, specifically a FeCrMoBC amorphous alloy.
[0102] Embodiment 2:
[0103] The present embodiment provides a wear-resistant universal joint, which includes a universal joint base 1 and universal joint petal teeth 2, wherein the universal joint petal teeth 2 are located above the universal joint base 1, and three universal joint petal teeth 2 are provided, which are evenly distributed along the circumference, and the angle between adjacent petal teeth is 120°, and the universal joint petal teeth 2 are inclined compared to the universal joint base 1; the surface of each universal joint petal tooth 2 is provided with a plurality of parallel oblique grooves 3, and the surface of the universal joint petal tooth 2 and the inner wall of the oblique groove 3 are coated with a composite coating, and the composite coating is composed of a high entropy alloy and an amorphous alloy.
[0104] The universal joint tooth 2 is in a convex shape and connected to the universal joint base 1 with a rounded corner. The width of the convexity first decreases, then increases, and finally decreases from bottom to top. The change in the width of the universal joint tooth 2 is achieved by an arc connection.
[0105] The inclination angle of the universal joint tooth 2 and the universal joint base 1 is 8°, and the inclination direction of the universal joint tooth 2 is consistent with the running direction of the motor rotor in the screw drilling tool.
[0106] There are four oblique grooves 3 on each universal joint tooth 2, which are evenly distributed on the surface of the universal joint tooth 2, and the width between two adjacent oblique grooves 3 is 3 cm.
[0107] The distance between the oblique groove 3 and the edge of the universal joint tooth 2 is 5 cm.
[0108] The oblique groove 3 is opened along the running direction of the motor rotor in the screw drill, and its inclination angle relative to the cross section of the universal joint base 1 is 45°.
[0109] The oblique groove 3 is in the shape of an elongated strip as a whole, and the width of the oblique groove 3 is 2 cm.
[0110] The slot opening of the oblique slot 3 has no right-angled area, and the long side and the short side of the oblique slot 3 are connected by a rounded corner, and the arc length of the rounded corner is 2.5 mm.
[0111] Three grooves 4 are arranged on the two long sides of the oblique groove 3 , and the width between adjacent grooves 4 is 1.5 mm.
[0112] The grooves 4 on the two long sides of the oblique groove 3 are parallel to each other and symmetrically arranged.
[0113] The thickness of the composite coating is 150 μm.
[0114] The composite coating on the surface of the universal joint tooth 2 is a first composite coating, and the content of the high entropy alloy in the first composite coating is 30wt%.
[0115] The surface of the universal joint base 1 is also coated with a first composite coating.
[0116] The composite coating on the inner wall of the oblique groove 3 is a second composite coating, and the content of high entropy alloy in the second composite coating is 70wt%.
[0117] The high entropy alloy in the composite coating is a WMoTaNb alloy, and specifically a VWMoTaNb high entropy alloy.
[0118] The amorphous alloy in the composite coating is a Ni-based alloy, specifically a NiCrP amorphous alloy.
[0119] Embodiment 3:
[0120] The present embodiment provides a wear-resistant universal joint, which includes a universal joint base 1 and universal joint petal teeth 2, wherein the universal joint petal teeth 2 are located above the universal joint base 1, and four universal joint petal teeth 2 are provided, which are evenly distributed along the circumference, and the angle between adjacent petal teeth is 90°, and the universal joint petal teeth 2 are inclined compared to the universal joint base 1; the surface of each universal joint petal tooth 2 is provided with a plurality of parallel oblique grooves 3, and the surface of the universal joint petal teeth 2 and the inner wall of the oblique groove 3 are coated with a composite coating, and the composite coating is composed of a high entropy alloy and an amorphous alloy.
[0121] The universal joint tooth 2 is in a convex shape and connected to the universal joint base 1 with a rounded corner. The width of the convexity first decreases, then increases, and finally decreases from bottom to top. The change in the width of the universal joint tooth 2 is achieved by an arc connection.
[0122] The inclination angle of the universal joint tooth 2 and the universal joint base 1 is 10°, and the inclination direction of the universal joint tooth 2 is consistent with the running direction of the motor rotor in the screw drilling tool.
[0123] There are two oblique grooves 3 on each universal joint tooth 2, which are evenly distributed on the surface of the universal joint tooth 2, and the width between two adjacent oblique grooves 3 is 5 cm.
[0124] The distance between the oblique groove 3 and the edge of the universal joint tooth 2 is 5.5 cm.
[0125] The oblique groove 3 is opened along the running direction of the motor rotor in the screw drill, and its inclination angle relative to the cross section of the universal joint base 1 is 20°.
[0126] The oblique groove 3 is in the shape of an elongated strip as a whole, and the width of the oblique groove 3 is 4 cm.
[0127] The slot opening of the oblique slot 3 has no right-angled area, and the long side and the short side of the oblique slot 3 are connected by a rounded corner, and the arc length of the rounded corner is 2 mm.
[0128] Four grooves 4 are arranged on the two long sides of the oblique groove 3 , and the width between adjacent grooves 4 is 1 mm.
[0129] The grooves 4 on the two long sides of the oblique groove 3 are parallel to each other and symmetrically arranged.
[0130] The thickness of the composite coating is 300 μm.
[0131] The composite coating on the surface of the universal joint tooth 2 is a first composite coating, and the content of the high entropy alloy in the first composite coating is 40wt%.
[0132] The surface of the universal joint base 1 is also coated with a first composite coating.
[0133] The composite coating on the inner wall of the oblique groove 3 is a second composite coating, and the content of high entropy alloy in the second composite coating is 60wt%.
[0134] The high entropy alloy in the composite coating is a FeCoNiCr alloy, and specifically a FeCoNiCrMn high entropy alloy.
[0135] The amorphous alloy in the composite coating is a Zr-based alloy, specifically a ZrCuNiAl amorphous alloy.
[0136] Embodiment 4:
[0137] This embodiment provides a method for preparing a wear-resistant universal joint surface coating, wherein the universal joint is the universal joint in Embodiment 1, and the preparation method comprises the following steps:
[0138] (1) The universal joint is ultrasonically cleaned in acetone and ethanol for 15 minutes respectively, the ultrasonic power is 120W, the ultrasonic frequency is 40kHz, and then the universal joint is fixed on a workbench for sandblasting roughening treatment, the sandblasting roughening uses quartz sand as the sandblasting medium, the average particle size of the quartz sand is 1.5mm, and the surface roughness of the universal joint after the sandblasting roughening treatment is 6.5μm; and high entropy alloy powder and amorphous alloy powder are mixed in different proportions, the high entropy alloy powder is FeCoNiCr alloy powder, the amorphous alloy powder is Fe-based alloy powder, and the average particle size of both is 30μm, the high entropy alloy powder accounts for 20wt% and the amorphous alloy powder accounts for 80wt% to prepare a high entropy amorphous alloy composite powder, and the high entropy alloy powder accounts for 80wt% and the amorphous alloy powder accounts for 20wt% to prepare another high entropy amorphous alloy composite powder, and the high entropy alloy powder and the amorphous alloy powder are mixed by ball milling for 5h;
[0139] (2) placing a composite powder in which a high entropy alloy powder accounts for 20wt% and an amorphous alloy powder accounts for 80wt% into a thermal spraying device, adjusting the equipment parameters until the composite powder flame flow reaches a stable state, placing the universal joint flap teeth just above the flame flow for thermal spraying, wherein the powder feeding rate during the thermal spraying is 100g / min, the spraying distance is 200mm, the moving speed of the spray gun is 500mm / s, the flow rate of hydrogen during the thermal spraying is 35L / min, the flow rate of nitrogen is 30L / min, the temperature range of the thermal spraying is 3000-3050°C, and the single spraying thickness is 10μm, thereby preparing a first composite coating;
[0140] (3) Put another composite powder in which the high entropy alloy powder accounts for 80wt% and the amorphous alloy powder accounts for 20wt% into the thermal spraying equipment, and adjust the equipment parameters until the composite powder flame flow reaches a stable state. The direction of the flame flow is inclined by 45° compared with the flame flow direction in step (2) so that it is aligned with the inner wall of the oblique groove for thermal spraying. The powder feeding rate during the thermal spraying is 100g / min, the spraying distance is 200mm, the moving speed of the spray gun is 500mm / s, the flow rate of hydrogen during the thermal spraying is 35L / min, the flow rate of nitrogen is 30L / min, the temperature range of the thermal spraying is 3000-3050℃, and the single spraying thickness is 10μm, so as to prepare a second composite coating.
[0141] The composite coating prepared in this example was subjected to the following tests to test its performance:
[0142] Detection 1: Microscopic morphology detection
[0143] The surface and cross section of the composite coating prepared in this example were observed and tested using a scanning electron microscope (SEM, ZEISS, JSM-IT700HR, Japan).
[0144] In this embodiment, the composite coating has a good surface morphology, has no obvious defects such as pits, pores, cracks and unmelted particles, and has good interface bonding.
[0145] Test 2: Mechanical properties
[0146] The universal joint coated with the composite coating of this embodiment was placed in a microhardness tester, the load was set to 200g, the loading time was 15s, and the average value was taken by measuring five times; it was placed in a nanoindenter, the indentation depth was set to 1500nm, and the nanohardness and elastic modulus were tested, and the average value was taken by measuring 5 times.
[0147] In this embodiment, after the above tests, the microhardness of the first composite coating is 868.7 HV, the nanohardness is 8.59 GPa, and the elastic modulus is 181.9 GPa; the microhardness of the second composite coating is 715.8 HV, the nanohardness is 6.91 GPa, and the elastic modulus is 117.5 GPa.
[0148] Test 3: Tribological properties
[0149] The universal joint coated with the composite coating of this embodiment was put into a friction and wear testing machine for friction and wear experiments. The set parameters were: wear scar length 5 mm, frequency 6 Hz, time 30 min, load 6 N, and the grinding balls were GCr15 and Si3N4 with a diameter of 6 mm.
[0150] In this embodiment, the friction and wear experiment shows that the friction and wear volume of the first composite coating is 4.52×10 -4 mm 3 The friction and wear volume of the second composite coating is 6.93×10 -4 mm 3 , that is, the friction and wear performance of the first composite coating is better than that of the second composite coating. When the proportion of amorphous alloy is higher, the wear resistance is higher.
[0151] Test 4: Corrosion performance
[0152] The universal joint coated with the composite coating of this embodiment was put into a corrosion and wear tester and an electrochemical workstation for testing. The corrosion and wear test parameters were consistent with those of the friction and wear test. A corrosion solution was added, and drilling fluid was selected specifically. The solution used in the electrochemical workstation was consistent with that in the electrochemical test. The electrochemical test parameters were: AC amplitude of 10 mV, initial frequency of 10 5 Hz, the end frequency is 10 -2Hz; when performing potentiodynamic polarization test, set the potential interval to 0.5mV, the initial potential to -0.5V, the termination potential to 1V, and the scan rate to 1mV / s.
[0153] In this embodiment, the corrosion and wear test shows that the corrosion and wear volume of the first composite coating is 2.83×10 -4 mm 3 The corrosion wear volume of the second composite coating is 6.31×10 -4 mm 3 That is, the corrosion and wear performance of the first composite coating is also better than that of the second composite coating. At this time, wear is still the main factor, so the performance of the first composite coating with a higher amorphous alloy content is better.
[0154] The above electrochemical tests show that the corrosion potential of the first composite coating is -0.6184 V and the corrosion current density is 1.832×10 -6 A.cm -2 The corrosion potential of the second composite coating is -0.4657 V, and the corrosion current density is 8.948×10 - 7 A.cm -2 At this time, the corrosion resistance of the second composite coating is better than that of the first composite coating. At this time, corrosion is the main factor, so the performance of the second composite coating with a higher high-entropy alloy content is better.
[0155] Test 5: Erosion performance
[0156] The universal joint coated with the composite coating of this embodiment was placed in an MLD-10 erosion testing machine for erosion testing. The experimental parameters were 200 r / min, the linear speed of the sample center axis was 1.68 m / s, the erosion time was 4 h, and the external factors selected were erosion angle, sand content and pH value.
[0157] Taking pH values of 9, 10, and 11 as examples, when the erosion angle is 90° and the sand content is 50%, the erosion weight loss rate of the composite coating decreases with the increase of pH. When the pH is 11, the erosion weight loss rate of the first composite coating is 0.0389 mg / h, and the erosion weight loss rate of the second composite coating is 0.0093 mg / h. Since the high entropy alloy mainly plays a corrosion-resistant role, the second composite coating with a higher high entropy alloy content has better erosion resistance.
[0158] Embodiment 5:
[0159] This embodiment provides a method for preparing a wear-resistant universal joint surface coating, wherein the universal joint is the universal joint in Embodiment 2, and the preparation method comprises the following steps:
[0160] (1) The universal joint is ultrasonically cleaned in acetone and ethanol for 10 minutes respectively, the ultrasonic power is 150W, the ultrasonic frequency is 50kHz, and then the universal joint is fixed on a workbench for sandblasting roughening treatment, the sandblasting roughening uses quartz sand as the sandblasting medium, the average particle size of the quartz sand is 1.2mm, and the surface roughness of the universal joint after the sandblasting roughening treatment is 5.0μm; and high entropy alloy powder and amorphous alloy powder are mixed in different proportions, the high entropy alloy powder is WMoTaNb alloy powder, the amorphous alloy powder is Ni-based alloy powder, and the average particle size of both is 20μm, the high entropy alloy powder accounts for 30wt% and the amorphous alloy powder accounts for 70wt% to prepare a high entropy amorphous alloy composite powder, the high entropy alloy powder accounts for 70wt% and the amorphous alloy powder accounts for 30wt% to prepare another high entropy amorphous alloy composite powder, and the high entropy alloy powder and the amorphous alloy powder are mixed by ball milling for 4h;
[0161] (2) placing a composite powder in which a high entropy alloy powder accounts for 30wt% and an amorphous alloy powder accounts for 70wt% into a thermal spraying device, adjusting the equipment parameters until the composite powder flame flow reaches a stable state, placing the universal joint flap teeth just above the flame flow for thermal spraying, wherein the powder feeding rate during the thermal spraying is 50g / min, the spraying distance is 180mm, the moving speed of the spray gun is 300mm / s, the flow rate of hydrogen during the thermal spraying is 40L / min, the flow rate of nitrogen is 20L / min, the temperature range of the thermal spraying is 3600-3650°C, the single spraying thickness is 12μm, and a first composite coating is prepared;
[0162] (3) Put another composite powder in which the high entropy alloy powder accounts for 70wt% and the amorphous alloy powder accounts for 30wt% into the thermal spraying equipment, and adjust the equipment parameters until the composite powder flame flow reaches a stable state. The direction of the flame flow is inclined by 40° compared with the flame flow direction in step (2) so that it is aligned with the inner wall of the oblique groove for thermal spraying. The powder feeding rate during the thermal spraying is 50g / min, the spraying distance is 180mm, the moving speed of the spray gun is 300mm / s, the flow rate of hydrogen during the thermal spraying is 40L / min, the flow rate of nitrogen is 20L / min, the temperature range of the thermal spraying is 3600-3650℃, and the single spraying thickness is 12μm, thereby preparing a second composite coating.
[0163] The composite coating prepared in this example was also subjected to performance testing in the same manner as in Example 4.
[0164] Through microscopic morphology detection, it can be seen that the surface morphology of the composite coating is good, without obvious defects such as pits, pores, cracks and unmelted particles, and the interface bonding is good;
[0165] According to the mechanical property test, the microhardness of the first composite coating is 822.6HV, the nanohardness is 8.26GPa, and the elastic modulus is 173.2GPa; the microhardness of the second composite coating is 746.7HV, the nanohardness is 7.16GPa, and the elastic modulus is 139.3GPa;
[0166] The tribological performance test shows that the friction and wear volume of the first composite coating is 5.39×10 -4 mm 3 The friction and wear volume of the second composite coating is 6.58×10 -4 mm 3 ;
[0167] The corrosion and wear test showed that the corrosion and wear volume of the first composite coating was 3.46×10 -4 mm 3 The corrosion wear volume of the second composite coating is 5.67×10 -4 mm 3 ; According to electrochemical tests, the corrosion potential of the first composite coating is -0.5833V, and the corrosion current density is 1.541×10 -6 A.cm -2 The corrosion potential of the second composite coating is -0.5108 V, and the corrosion current density is 9.748×10 -7 A.cm -2 ;
[0168] Through the erosion performance test, it can be seen that, taking the pH values of 9, 10 and 11 as examples, when the erosion angle is 90° and the sand content is 50%, the erosion weight loss rate of the composite coating decreases with the increase of pH. When the pH is 11, the erosion weight loss rate of the first composite coating is 0.0276 mg / h, and the erosion weight loss rate of the second composite coating is 0.0137 mg / h.
[0169] Embodiment 6:
[0170] This embodiment provides a method for preparing a wear-resistant universal joint surface coating, wherein the universal joint is the universal joint in Embodiment 3, and the preparation method comprises the following steps:
[0171] (1) The universal joint is ultrasonically cleaned in a mixture of acetone and ethanol for 30 minutes, wherein the power of the ultrasound is 100 W and the frequency of the ultrasound is 30 kHz, and then the universal joint is fixed on a workbench for sandblasting roughening treatment, wherein the sandblasting medium used for the sandblasting roughening is quartz sand, and the average particle size of the quartz sand is 1.8 mm. After the sandblasting roughening treatment, the surface roughness of the universal joint is 8.0 μm; and high entropy alloy powder and amorphous alloy powder are mixed in different proportions, wherein the high entropy alloy powder is FeCoNiCr alloy powder, and the amorphous alloy powder is Zr-based alloy powder, and the average particle size of both is 40 μm, and the high entropy alloy powder accounts for 40wt% and the amorphous alloy powder accounts for 60wt% to prepare a high entropy amorphous alloy composite powder, and the high entropy alloy powder accounts for 60wt% and the amorphous alloy powder accounts for 40wt% to prepare another high entropy amorphous alloy composite powder, and the high entropy alloy powder and the amorphous alloy powder are mixed by ball milling for 6 hours;
[0172] (2) placing a composite powder in which a high entropy alloy powder accounts for 40wt% and an amorphous alloy powder accounts for 60wt% into a thermal spraying device, adjusting the equipment parameters until the composite powder flame flow reaches a stable state, placing the universal joint flap teeth just above the flame flow for thermal spraying, wherein the powder feeding rate during the thermal spraying is 150g / min, the spraying distance is 230mm, the moving speed of the spray gun is 800mm / s, the flow rate of hydrogen during the thermal spraying is 25L / min, the flow rate of nitrogen is 40L / min, the temperature range of the thermal spraying is 2550-2600°C, the single spraying thickness is 8μm, and a first composite coating is prepared;
[0173] (3) Put another composite powder in which the high entropy alloy powder accounts for 60wt% and the amorphous alloy powder accounts for 40wt% into the thermal spraying equipment, and adjust the equipment parameters until the composite powder flame flow reaches a stable state. The direction of the flame flow is inclined by 50° compared with the flame flow direction in step (2) so that it is aligned with the inner wall of the oblique groove for thermal spraying. The powder feeding rate during the thermal spraying is 150g / min, the spraying distance is 230mm, the moving speed of the spray gun is 800mm / s, the flow rate of hydrogen during the thermal spraying is 25L / min, the flow rate of nitrogen is 40L / min, the temperature range of the thermal spraying is 2550-2600℃, and the single spraying thickness is 8μm, thereby preparing a second composite coating.
[0174] The composite coating prepared in this example was also subjected to performance testing in the same manner as in Example 4.
[0175] Through microscopic morphology detection, it can be seen that the surface morphology of the composite coating is good, without obvious defects such as pits, pores, cracks and unmelted particles, and the interface bonding is good;
[0176] The mechanical properties test showed that the microhardness of the first composite coating was 801.3 HV, the nanohardness was 7.97 GPa, and the elastic modulus was 168.1 GPa; the microhardness of the second composite coating was 770.5 HV, the nanohardness was 7.53 GPa, and the elastic modulus was 150.5 GPa;
[0177] The tribological performance test shows that the wear volume of the first composite coating is 4.98×10 -4 mm 3 The wear volume of the second composite coating is 6.01×10 -4 mm 3 ;
[0178] The corrosion and wear test showed that the corrosion and wear volume of the first composite coating was 3.92×10 -4 mm 3 The corrosion wear volume of the second composite coating is 5.21×10 -4 mm 3 ; According to electrochemical tests, the corrosion potential of the first composite coating is -0.5679V, and the corrosion current density is 1.127×10 -6 A.cm -2 The corrosion potential of the second composite coating is -0.5348 V, and the corrosion current density is 1.108×10 -6 A.cm -2 ;
[0179] Through the erosion performance test, it can be seen that, taking pH values of 9, 10 and 11 as examples, when the erosion angle is 90° and the sand content is 50%, the erosion weight loss rate of the composite coating decreases with the increase of pH. When the pH is 11, the erosion weight loss rate of the first composite coating is 0.0207 mg / h, and the erosion weight loss rate of the second composite coating is 0.0185 mg / h.
[0180] From the above embodiments, it can be seen that the present invention optimizes the design of the universal joint structure. Through the petal tooth design on the universal joint and the setting of the oblique grooves on the petal teeth, the contact area between the petal teeth of the universal joint and between the drilling fluid and the universal joint is increased while ensuring the overall structural strength and rigidity of the universal joint, thereby reducing the erosion and corrosion effects of the drilling fluid on the surface of the universal joint; by coating a composite coating on the surface of the universal joint and selecting different contents of high entropy alloy and amorphous alloy, the wear resistance, corrosion resistance and erosion resistance of the universal joint are further improved, the overall microhardness of the coating is above 715.0HV, the nanohardness is above 6.9GPa, and the elastic modulus can reach above 117.0GPa, which effectively reduces the surface friction coefficient, improves the transmission efficiency, and increases the service life of the universal joint, so that it can better adapt to complex and changeable service environments; the universal joint structure is reasonably designed, the improvement method is simple, the improvement effect is significant, and the scope of application is wide.
[0181] The applicant declares that the present invention illustrates the detailed structure and method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed structure and method, that is, it does not mean that the present invention must rely on the above-mentioned detailed structure and method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the structure of the present invention, addition of auxiliary structure, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A wear-resistant universal joint, characterized in that: The universal joint includes a universal joint base and universal joint petals, wherein the universal joint petals are located above the universal joint base, and at least three universal joint petals are provided, which are evenly distributed along the circumference, and the universal joint petals are inclined compared to the universal joint base; the surface of each universal joint petal is provided with a plurality of parallel oblique grooves, and the surface of the universal joint petal and the inner wall of the oblique groove are coated with a composite coating, and the composite coating is composed of a high entropy alloy and an amorphous alloy.
2. The universal joint according to claim 1, characterized in that: The universal joint petal teeth are in a convex shape and connected to the universal joint base body with rounded corners. The width of the convexity decreases from bottom to top, then increases, and finally decreases again. Preferably, the change in the width of the universal joint petal teeth is achieved by using an arc connection; Preferably, the inclination angle of the universal joint petal teeth relative to the universal joint base is 5-10°, and the inclination direction of the universal joint petal teeth is consistent with the running direction of the motor rotor in the screw drilling tool.
3. The universal joint according to claim 1 or 2, characterized in that: The number of the oblique grooves on each of the universal joint petal teeth is at least two, which are evenly distributed on the surface of the universal joint petal teeth, and the width between two adjacent oblique grooves is not less than 3 cm; Preferably, the distance between the oblique groove and the edge of the universal joint tooth is not less than 5 cm; Preferably, the oblique groove is opened along the running direction of the motor rotor in the screw drill, and its inclination angle compared with the cross section of the universal joint base is 20-45°.
4. The universal joint according to any one of claims 1 to 3, characterized in that: The oblique groove is in the shape of an elongated strip as a whole, and the width of the oblique groove is 2 to 4 cm; Preferably, the notch of the oblique groove has no right-angle area, the long side and the short side of the oblique groove are connected by a rounded corner, and the arc length of the rounded corner is not greater than 3 mm; Preferably, at least two grooves are provided on the two long sides of the oblique groove, and the width between adjacent grooves is not greater than 2 mm; Preferably, the grooves on the two long sides of the oblique groove are parallel to each other and symmetrically arranged.
5. The universal joint according to any one of claims 1 to 4, characterized in that: The thickness of the composite coating is 150 to 300 μm; Preferably, the content of high entropy alloy in the composite coating is 20-80wt%; Preferably, the composite coating on the surface of the universal joint tooth is a first composite coating, and the content of the high entropy alloy in the first composite coating is 20-40wt%; Preferably, the surface of the universal joint substrate is also coated with a first composite coating; Preferably, the composite coating on the inner wall of the oblique groove is a second composite coating, and the content of the high entropy alloy in the second composite coating is 60-80wt%; Preferably, the high entropy alloy in the composite coating comprises a FeCoNiCr alloy or a WMoTaNb alloy; Preferably, the amorphous alloy in the composite coating includes any one of Fe-based alloy, Ni-based alloy or Zr-based alloy or a combination of at least two thereof; Preferably, the composite coating is made of high entropy amorphous alloy composite powder obtained by uniformly mixing high entropy alloy powder and amorphous alloy powder.
6. The method for preparing the surface coating of a universal joint according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) After the universal joint is fixed, a sandblasting roughening treatment is performed, and high entropy alloy powder and amorphous alloy powder are mixed in different proportions to prepare two high entropy amorphous alloy composite powders; (2) thermally spraying one of the high entropy amorphous alloy composite powders onto the surface of the universal joint tooth to prepare a first composite coating; (3) Another high entropy amorphous alloy composite powder is thermally sprayed onto the inner wall of the oblique groove of the universal joint to prepare a second composite coating.
7. The preparation method according to claim 6, characterized in that: The universal joint in step (1) is cleaned before being fixed; Preferably, the cleaning comprises ultrasonic cleaning using an organic solvent; Preferably, the organic solvent comprises acetone and / or ethanol; Preferably, the power of the ultrasound is 100-150W, and the frequency of the ultrasound is 30-50kHz; Preferably, the cleaning time is 10 to 30 minutes; Preferably, when the universal joint is fixed in step (1), the universal joint base is fixed on a workbench; Preferably, the sandblasting roughening in step (1) uses a sandblasting medium comprising quartz sand; Preferably, the particle size of the sandblasting medium is 1 to 2 mm; Preferably, after the sandblasting roughening treatment in step (1), the surface roughness of the universal joint is 4.5 to 8.5 μm.
8. The preparation method according to claim 6 or 7, characterized in that: The particle sizes of the high entropy alloy powder and the amorphous alloy powder in step (1) are independently 15 to 45 μm; Preferably, the high entropy alloy powder comprises FeCoNiCr alloy powder or WMoTaNb alloy powder; Preferably, the amorphous alloy powder includes any one of Fe-based alloy powder, Ni-based alloy powder or Zr-based alloy powder, or a combination of at least two thereof; Preferably, in the two high entropy amorphous alloy composite powders in step (1), the high entropy alloy powder accounts for 20-40wt% in one composite powder, and the high entropy alloy powder accounts for 60-80wt% in the other composite powder; Preferably, the high entropy alloy powder and the amorphous alloy powder are mixed in step (1) by ball milling; Preferably, the ball milling mixing time is 4 to 6 hours.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The thermal spraying in step (2) is performed using a thermal spraying device, and the parameters of the thermal spraying device are debugged before the thermal spraying; Preferably, the composite powder in step (2) is placed in a thermal spraying device, and the device parameters are adjusted until the composite powder flame flow reaches a stable state; Preferably, in step (2), the thermal spraying uses a composite powder in which the high entropy alloy powder accounts for 20-40 wt%, and the universal joint tooth is placed directly above the flame flow; Preferably, after the universal joint petal teeth are coated in step (2), the universal joint substrate is coated, and the process parameters for coating the universal joint substrate are the same as the corresponding parameters for the universal joint petal teeth; Preferably, during the thermal spraying in step (2), the powder feeding rate is 50-150 g / min, the spraying distance is 180-230 mm, and the moving speed of the spray gun is 300-800 mm / s; Preferably, in step (2), fuel gas and carrier gas are used during the thermal spraying, the fuel gas comprises hydrogen, and the carrier gas comprises nitrogen and / or an inert gas; Preferably, the flow rate of the fuel gas is 25 to 45 L / min, and the flow rate of the carrier gas is 20 to 40 L / min; Preferably, the temperature of the thermal spraying in step (2) is 2500-4000°C; Preferably, the single spraying thickness during the thermal spraying in step (2) is 8 to 12 μm.
10. The preparation method according to any one of claims 6 to 9, characterized in that: In step (3), the thermal spraying uses a composite powder in which the high entropy alloy powder accounts for 60 to 80 wt%, and adjusts the direction of the flame flow in step (2) so that it is aligned with the inner wall of the oblique groove; Preferably, the direction of the flame flow in step (3) is inclined by 40 to 50° compared to the direction of the flame flow in step (2); Preferably, during the thermal spraying in step (3), the powder feeding rate is 50-150 g / min, the spraying distance is 180-230 mm, and the moving speed of the spray gun is 300-800 mm / s; Preferably, in step (3), fuel gas and carrier gas are used during the thermal spraying, the fuel gas comprises hydrogen, and the carrier gas comprises nitrogen and / or an inert gas; Preferably, the flow rate of the fuel gas is 25 to 45 L / min, and the flow rate of the carrier gas is 20 to 40 L / min; Preferably, the temperature of the thermal spraying in step (3) is 2500-4000°C; Preferably, the single spraying thickness during the thermal spraying in step (3) is 8 to 12 μm.
Citation Information
Patent Citations
Amorphous alloy coating and preparation method thereof
CN115141998A
Cardan shaft shell body
CN202946039U